Factors Associated With, and Mitigation Strategies for, Health Care Disparities Faced by Patients With Headache Disorders. (10th August 2021) - Kiarashi, Jessica; VanderPluym, Juliana; Szperka, Christina L.; Turner, Scott; Minen, Mia T.; Broner, Susan; Ross, Alexandra C.; Wagstaff, Amanda E.; Anto, Marissa; Marzouk, Maya; Monteith, Teshamae S.; Rosen, Noah; et al.
Abstract : Objective: To review contemporary issues of health care disparities in headache medicine with regard to race/ethnicity, socioeconomic status (SES), and geography and propose solutions for addressing these disparities. Methods: An Internet and PubMed search was performed and literature was reviewed for key concepts underpinning disparities in headache medicine. Content was refined to areas most salient to our goal of informing the provision of equitable care in headache treatment through discussions with a group of 16 experts from a range of headache subspecialties. Results: Taken together, a multitude of factors, including racism, SES, insurance status, and geographical disparities, contribute to the inequities that exist within the health care system when treating headache disorders. Interventions such as improving public education, advocacy, optimizing telemedicine, engaging in community outreach to educate primary care providers, training providers in cultural sensitivity and competence and implicit bias, addressing health literacy, and developing recruitment strategies to increase representation of underserved groups within headache research are proposed as solutions to ameliorate disparities. Conclusion: Neurologists have a responsibility to provide and deliver equitable care to all. It is important that disparities in the management of headache disorders are identified and addressed.